Metastatic patterns and prognosis of patients with primary malignant cardiac tumor - Guan, Tianwang; Wei, Qingqian; Tang, Yongshi; Zhao, Hongjun; Lu, Zhenxing; Feng, Weijing; Teng, Yintong; Luo, Zehao; Chi, Kaiyi; Ou, Caiwen; Chen, Minsheng (Frontiers in Cardiovascular Medicine, 2022)
Background: Distant metastasis is an independent negative prognostic factor for patients with primary malignant cardiac tumors (PMCT). This study aims to further investigate metastatic patterns and their prognostic effects in patients with PMCT. Methods: This multicenter retrospective study included 218 patients with PMCT diagnosed between 2010 and 2017 from Surveillance, Epidemiology, and End Results (SEER) database. Logistic regression was utilized to identify metastatic risk factors. A Chi-square test was performed to assess the metastatic rate. Kaplan–Meier methods and Cox regression analysis were used to analyze the prognostic effects of metastatic patterns. Results: Sarcoma (p = 0.002) and tumor size＞4 cm (p = 0.006) were independent risk factors of distant metastasis in patients with PMCT. Single lung metastasis (about 34%) was the most common of all metastatic patterns, and lung metastasis occurred more frequently (17.9%) than bone, liver, and brain. Brain metastasis had worst overall survival (OS) and cancer-specific survival (CSS) among other metastases, like lung, bone, liver, and brain (OS: HR=3.20, 95% CI: 1.02-10.00, p = 0.046; CSS: HR=3.53, 95% CI: 1.09-11.47, p = 0.036). Conclusions: Patients with PMCT who had sarcoma or a tumor larger than 4 cm had a higher risk of distant metastasis. Lung was the most common metastatic site, and brain metastasis had worst survival among others, such as lung, bone, liver, and brain. The results of this study provide insight for early detection, diagnosis, and treatment of distant metastasis associated with PMCT.